2010
DOI: 10.1097/iae.0b013e3181b9f16b
|View full text |Cite
|
Sign up to set email alerts
|

Vitreoretinal Surgery in Eyes With Pintucci Biointegrable Keratoprosthesis

Abstract: Vitreoretinal surgery in eyes with Pintucci biointegrable keratoprosthesis is a highly challenging situation that requires intricate planning and an integrated approach. However, it can result in good anatomical and functional outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…8 In managing these cases, we have drawn from our past experience with management of eyes with BKP and the other types of permanent keratoprosthesis. 2,9,10 The mean time interval between KP implant and the occurrence of VR complication(s) in our study was 8 months. Goldman et al have reported the same to be 5.6 months in their study.…”
Section: Discussionmentioning
confidence: 64%
“…8 In managing these cases, we have drawn from our past experience with management of eyes with BKP and the other types of permanent keratoprosthesis. 2,9,10 The mean time interval between KP implant and the occurrence of VR complication(s) in our study was 8 months. Goldman et al have reported the same to be 5.6 months in their study.…”
Section: Discussionmentioning
confidence: 64%
“…2,4 In post-Pintucci biointegrable keratoprosthesis eyes, time to VR complications ranged from 10 days to 8 months. 10 In the 41 post-OOKP eyes (45%) that had VR complications, 26 of 41 eyes (63%) had 34 of 59 complication episodes (57%) and required surgical management. In other words, 34 of 92 post-mOOKP surgery eyes (37%) required surgical VR intervention.…”
Section: Discussionmentioning
confidence: 96%
“…42,55,73,74 Vitrectomy with a permanent KPro is safe and has no deleterious effects on the donor cornea/graft KPro device. Cohort studies report the incidence of vitrectomy after KPro placement to be around 7%.…”
Section: 2mentioning
confidence: 98%